PENGEMBANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DI SMK - Suharti; Hasanah Nur (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This research aims to: (1) Develop a website-based library information system that provides easy data management for librarians to make library users more productive; (2) Develop a website-based library information system that meets ISO 9126 standards. The type of research used in this study is Research and Development (R&D). Data collection techniques applied are field observation, related party interviews and documentation. This research develops a website-based library information system, which aims to make it easier for librarians to manage data and so that local library visitors get information quickly and accurately. Based on the results of the study, the value of the functionality aspect is close to number 1 with the category according to the eligibility requirements. The usability aspect value is 89% with a very good category. Assessment of efficienc aspects The average efficiency of web page load time of 2,225 seconds is up to standard. Assessment of portability aspects, information systems can be operated on all devices